The Effectiveness of the Use of Video Media on Learning on the Competence of Scalp and Hair Care of Vocational High School Students of Beauty Department - Nurhayati, Ifa; Khumaedi, Muhammad; Yudiono, Heri (Universitas Negeri Semarang, 2018)
The objective of this study is to determine the effectiveness of the use of video media in improving student learning outcomes in the competence of caring for the scalp and hair. The research method used was an experimental method with pretest and posttest control group design. This study used test as a research data collection instrument. The validity test of the test questions was analyzed by using product moment correlation and the reliability testi was analyzed by using the Kuder-Richardson-20 formula (KR-20). The contents validity of video instrument and the performance of students were analyzed by using the Contents Validity Ratio (CVR) formula, meanwhile, the reliability test was analyzed by using Cohens Kappa. The study population was a class of X beauty students at State Vocational High School 3 Pati. The placement of the students into the experiment group and the control group used a random assigment technique by drawing. Based on the results of the t-test, the initial average of learning outcomes in the competency of caring the scalp and hair of the control group is 54.5704, it improves into 75.0593 with the improves of 37.54%, including in the â€œlowâ€ category. Whereas, in the experiment group, the initial average learning outcomes in the competency of caring for the scalp and hair is 55.9438, it increases to 83.3281, with the improves of 48.95%, including in the â€œmediumâ€ category. The difference in the improvement in learning outcomes in the experiment group is higher than the difference in the improvement in learning outcomes of the control group (48.95% > 37.54%) so that it can be synthesized that the use of video media is effective in learning competency in caring for the scalp and hair in class of X beauty students of State Vocational High School 3 Pati.